Old State House at 206 Washington Street, ca. 1885 - Unknown (Tufts Archival Research Center, 2005)
Elevated view west-northwest of the Old State House, located at 206 Washington Street. A balcony, two statues, signage and a clock adorn the east elevation of the building. Buildings lining the north side of State Street are included along the right side of the photograph, while buildings lining the west side of Washington Street are visible in the background of the photograph. A street light is located beside the southeast corner of the Old State House. Copyprint 9 7/16 x 6 15/16, 10 x 8 overall Photographs